2018
DOI: 10.1136/bmjopen-2017-021193
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol to assess the effectiveness and safety of a flexible family visitation model for delirium prevention in adult intensive care units: a cluster-randomised, crossover trial (The ICU Visits Study)

Abstract: IntroductionFlexible intensive care unit (ICU) visiting hours have been proposed as a means to improve patient-centred and family-centred care. However, randomised trials evaluating the effects of flexible family visitation models (FFVMs) are scarce. This study aims to compare the effectiveness and safety of an FFVM versus a restrictive family visitation model (RFVM) on delirium prevention among ICU patients, as well as to analyse its potential effects on family members and ICU professionals.Methods and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
13
0
3
Order By: Relevance
“…Details of trial rationale and methods have been reported previously. 14 The ICU Visits study was conducted from April 2017 to July 2018 in 36 mixed Brazilian ICUs after approval by institutional review boards of all centers. All participating ICU clinicians provided written informed consent for study participation.…”
Section: Methodsmentioning
confidence: 99%
“…Details of trial rationale and methods have been reported previously. 14 The ICU Visits study was conducted from April 2017 to July 2018 in 36 mixed Brazilian ICUs after approval by institutional review boards of all centers. All participating ICU clinicians provided written informed consent for study participation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, according to other studies, family members feel relaxed and less anxious if they visit their patients in the intensive care units. 29,66 Therefore, it is necessary to implement some strategies to reduce the limitations of ICU visiting policies and increase the presence of family members at the patient's bedside to enhance their communication and participation in patient care. This is because visitation based on a very strict and limited policy, such as the current visitation policies commonly practiced, 13,59,61,67 seems to be inefficient in meeting the needs of the ICU patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…13,27 Some other studies have shown that ICU nurses perceive patients' visits as a source of increased workload and burnout. 28,29 Disorganization of patient care and more interruptions due to the extended presence of families in the ICU are the other reasons for adhering strict visiting policy in intensive care units. 30 There is also concern that with open visitation policy, stress of family members will increase because of feeling to be obligated to stay in the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…The ICU Visits Study is a cluster-randomized, crossover trial comparing an FFVM (12 consecutive ICU visiting hours per day) with an RFVM (< 4.5 ICU visiting hours per day) in Brazilian adult ICUs. The study background, design, rationale, eligibility criteria, and sample size have been previously published [ 10 ]. In brief, mixed adult ICUs of public and private philanthropic hospitals with a restrictive policy of ICU visiting hours (< 4.5 h/day) are randomly assigned to either an FFVM or RFVM in a 1:1 ratio until the recruitment and follow-up of 25 patients (phase 1) (Fig.…”
Section: Trial Overviewmentioning
confidence: 99%